2009
DOI: 10.1002/jmv.21418
|View full text |Cite
|
Sign up to set email alerts
|

Increased detection of HBV DNA in HBsAg‐positive and HBsAg‐negative South African HIV/AIDS patients enrolling for highly active antiretroviral therapy at a Tertiary Hospital

Abstract: This retrospective study investigated the prevalence of hepatitis B virus (HBV) in 192 stored sera from human immunodeficiency virus (HIV) positive South African patients initiating antiretroviral therapy (ART), and explored the implications of HBV-HIV co-infection on laboratory diagnosis of HBV. HBV serology (HBsAg, anti-HBs and anti-HBc) and nested HBV PCR assays targeting the HBV polymerase gene were performed, with HBV DNA positive samples being quantified with Cobas Taqman HBV test 48 assay (Roche Diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
70
8
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 27 publications
18
70
8
1
Order By: Relevance
“…Tremeau-Bravard, A. et al in Nigeria in 2012, Muriuki et al in Kenya in 2013, Kapembwa et al in Zambia in 2011(Tremeau-Bravard, Ogbukagu, Ticao, & Abubaka, 2012Beatrice, Michael, Dorcas, Anthony, & Samoel, 2013;Kapembwa et al, 2011), who found respectively 7,9%; 6%; 9.9%. On the other hand, Lukhwareni et al (Lukhwareni, Burnett, Selabe, Mzileni, & Mphahlele, 2009) in South Africa in 2009, found a much higher prevalence than ours (22.9%).…”
Section: Discussioncontrasting
confidence: 74%
“…Tremeau-Bravard, A. et al in Nigeria in 2012, Muriuki et al in Kenya in 2013, Kapembwa et al in Zambia in 2011(Tremeau-Bravard, Ogbukagu, Ticao, & Abubaka, 2012Beatrice, Michael, Dorcas, Anthony, & Samoel, 2013;Kapembwa et al, 2011), who found respectively 7,9%; 6%; 9.9%. On the other hand, Lukhwareni et al (Lukhwareni, Burnett, Selabe, Mzileni, & Mphahlele, 2009) in South Africa in 2009, found a much higher prevalence than ours (22.9%).…”
Section: Discussioncontrasting
confidence: 74%
“…Previous studies in South Africa have shown that HBV DNA is significantly higher in HIV-infected than in HIV-negative patients, suggesting that HIV infection may be a risk factor for occult HBV infections. [12,16] This finding highlights the level of undetected active HBV infections that have the potential to affect antiretroviral therapy (ART) as their presence increases hepatotoxicity of ART with consequent limitation of their use. [17,18] Anti-HBs are known to confer protection against HBV at plasma levels ≥10 IU/ml.…”
Section: Discussionmentioning
confidence: 97%
“…This was followed by amplification of HBV core gene using an in-house nested polymerase chain reaction (PCR) protocol as previously described. [12] The nested PCR amplification product was verified for expected fragment size by a 1% ethidium bromide-stained agarose gel electrophoresis at a constant voltage of 100 V for 40 minutes, and viewed by UV transillumination.…”
Section: Determination Of Occult Hbv Infections In Hiv-infected Patientsmentioning
confidence: 99%
“…Of HIV-infected individuals, 66% 10,11 have evidence of either past or present infection with HBV. Because HBV vaccine has been included in the Expanded Programme on Immunization (EPI) in South Africa only since 1995, these individuals would not have been immunised at birth and would therefore have been susceptible to HBV infection.…”
mentioning
confidence: 99%
“…14 Deaths among HIV-infected people with chronic HBV and HCV infections, now seen as a result of end-stage liver disease, have increased worldwide. 15 Studies by Lukhwareni et al 10 strongly support the policy that all HIV-positive patients initiating highly active antiretroviral therapy (HAART) in South Africa be screened for HBV, and the Centers for Disease Control (CDC) in the USA recommend that all HIV-infected HCWs be vaccinated against HBV. 16 Studies on the impact of HIV/AIDS on the health sector in four provinces in South Africa in 2002 and in two public hospitals in Johannesburg in 2005 estimated the HIV seroprevalence among HCWs to be 15.7% 17 and 11.5% 18 respectively.…”
mentioning
confidence: 99%